1990
DOI: 10.1021/bi00461a023
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the D-alanyl-D-alanine-adding enzyme from Escherichia coli

Abstract: The Escherichia coli D-alanyl-D-alanine-adding enzyme, which catalyzes the final cytoplasmic step in the biosynthesis of the bacterial peptidoglycan precursor UDP-N-acetylmuramyl-L-Ala-gamma-D-Glu-meso-diaminopimelyl-D-Ala-D- Ala, has been purified to homogeneity from an E. coli strain that harbors a recombinant plasmid bearing the structural gene for this enzyme, murF. The enzyme is a monomer of molecular weight 49,000, and it has a turnover number of 784 min-1 for ATP-driven amide bond formation. Experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 25 publications
(30 reference statements)
4
50
0
Order By: Relevance
“…m g -' protein and the turnover number to 931 min-'. A turnover number of 784 min-' was previously determined for the MurF synthetase [24]. Under the most optimal in vitro conditions considered here, the D-glutamate-adding activity could catalyse the formation in each cell of approximately 28 x 10' peptidoglycan units during a 30-min generation time (2000 x 931 x 30).…”
Section: Discussionmentioning
confidence: 91%
“…m g -' protein and the turnover number to 931 min-'. A turnover number of 784 min-' was previously determined for the MurF synthetase [24]. Under the most optimal in vitro conditions considered here, the D-glutamate-adding activity could catalyse the formation in each cell of approximately 28 x 10' peptidoglycan units during a 30-min generation time (2000 x 931 x 30).…”
Section: Discussionmentioning
confidence: 91%
“…In E. coli, murein peptide ligase (Mpl) recycles the tri-, tetra-and pentapeptides by ligating them to UDP-MurNAc [179,180]. Another enzyme, MurF can also ligate dipeptide D-Ala-D-Ala (a product of ATP-dependent ligase Ddl), to a UDP-MurNAc tripeptide to form a UDP-MurNAc pentapeptide [181][182][183]. Homologues of Mpl (PA4020) and MurF (PA4416) and Ddl (PA4201/PA4410) are found in P. aeruginosa; however, their role in cell-wall recycling has not been elucidated.…”
Section: Convergence Of Recycling and Biosynthesismentioning
confidence: 99%
“…In cell-free MurF assay, each substrate was converted to the corresponding product, UDP-MurNAc-pentapeptide or UDP-MurNAc-dansylpentapeptide, which was confirmed by HPLC analysis. 30 This indicated that UDP-MurNAc-dansyltripeptide was used as the substrate of MurF, and suggested that MurF activity could be measured in a high-throughput mode by coupling translocase I.…”
Section: Resultsmentioning
confidence: 99%
“…HPLC detection of the MurF activity was carried out as described by Duncan et al 30 with slight modifications. The reaction mixture containing 100 mM TrisHCl (pH 8.6), 40 mM KCl, 10 mM MgCl 2 , 200mM UDP-MurNAc-tripeptide, 200 mM D-Ala-D-Ala, 200 mM ATP and 8% glycerol was added to 10 ml of MurF and incubated.…”
Section: Hplc Assaymentioning
confidence: 99%